ASIMILASI ARSITEKTUR DI LASEM JAWA TENGAH - Sophia Ratna Haryati (Sustainable, Planning and Culture (SPACE) : Jurnal Perencanaan Wilayah dan Kota, 2019)
The process of cultural acculturation and archipelago architecture began since the entry of traders who bring valueand cultural elements which then synergize with local culture. From history, we can see, many forms of archipelagoarchitecture has since opened up to the influence of the outer culture that comes in. The cities of Lasem, Tuban and Gresikin the North Coast in the Eastern part of Java Island are the cities that became the starting point of entry of foreigntraders. So do not be surprised if the shape of the architecture of the North Coast area in the eastern part of Java isheavily influenced by Chinese, Arabic, and Colonial cultural values. This is reinforced by historical data about the entryof 13th century Chinese culture, Arabic in the fifteenth century and the Dutch (VOC) in the 17th century. The entry ofChinese, Arab, and Dutch Culture to Indonesia in the glorious period of the Majapahit Kingdom gave a touch of changeand continuity in various cultural activities. Traces of relations between these cultures that eventually create a form ofacculturation of architecture that appears from the shape and meaning of existing buildings in the area of the North Coastin the Eastern part of Java Island. From the exploration process conducted by phenomenological approach that focuseson the process of acculturation of architecture, will be able to prove that Lasem Region is an expression of acculturationbetween Chinese culture, Middle East, Colonial, and Java through its concepts.